Exploration of the Potential of Hotong (Setaria italica) Based on Local Wisdom as a Functional Food for Stunting Prevention in Maluku - Jamaludin; Rony Marsyal Kunda; Jilian Risky Huwae; Milda Rianty Lakoan (Jurnal Penelitian Pendidikan IPA, 2025)
Stunting remains a major nutritional problem in Indonesia, particularly in vulnerable regions such as South Buru Regency, Maluku Province. Local food diversification represents a strategic approach to improving community nutrition and food security. This study evaluated the nutritional value and socio-ecological potential of Hotong (Setaria italica), a traditional cereal cultivated by local communities in Namrole District and adapted to dryland farming systems. A quantitative descriptive method was applied through a survey of 70 Hotong-farming households in Waenewen Hamlet, Labuang Village, Namrole District, Buru Regency, combined with proximate analysis of Hotong grains based on AOAC standards. The results showed that Hotong contains ash (1.33%), protein (11.60%), fat (3.43%), crude fiber (2.20%), and carbohydrates (65.31%). This nutritional composition indicates that Hotong can contribute up to 40% of protein requirements and approximately 35% of daily iron needs for toddlers aged 1–3 years. Furthermore, 86.67% of farmers reported annual production of ≥ 4 quintals despite relying on traditional cultivation practices, highlighting the crop’s availability and sustainability. These findings demonstrate that Hotong has significant potential as a functional local food for stunting prevention, while also reflecting cultural resilience and local wisdom in maintaining food systems under dryland conditions. Integrating Hotong into regional nutrition and food security programs, including the development of locally processed food products, may contribute to improving the nutritional status of toddlers in dryland areas.